Greyhounds under general veterinary care in the UK during 2016: demography and common disorders - Dan G. O’Neill; Nicola J. Rooney; Callum Brock; David B. Church; Dave C. Brodbelt; Camilla Pegram (Canine Genetics and Epidemiology, 2019)
Abstract Background The greyhound is a sighthound known for its speed and agility. Greyhounds were selectively bred as functional racing animals but increasingly are kept as pets in the UK, often after their racing careers are over. The VetCompass™ Programme collates de-identified clinical data from primary-care veterinary practices in the UK for epidemiological research. Using VetCompass™ clinical data, this study aimed to characterise the demography, mortality and common disorders of the general population of pet greyhounds under veterinary care in the UK. Results Greyhounds comprised 5419/ 905,544 (0.60%) dogs under veterinary care during 2016 from 626 clinics. Mean adult bodyweight was 29.7 kg (standard deviation [SD] 4.5 kg). Males (32.3 kg, SD 4.1 kg) were heavier than females (27.2 kg, SD 3.3 kg) (P < 0.001). Mean age was 7.6 years (SD 3.4). The most common colours were black (39.2%), black and white (20.8%), brindle (12.0%). Based on 474 deaths, median longevity was 11.4 years (range 0.2–16.5). Females (11.8 years) outlived males (11.2 years) (P = 0.002). The most common grouped causes of death were neoplasia (21.5%, 95% CI: 17.4–26.0), collapse (14.3%, 95% CI: 10.9–18.2) and musculoskeletal disorder (7.8%, 95% CI: 5.3–11.0). Based on a random subset of 2715/5419 (50.1%) greyhounds, 77.5% had > 1 disorder recorded during 2016. The most prevalent specific disorders were periodontal disease (39.0%, 95% CI: 37.2–40.9), overgrown nails (11.1%, 95% CI 10.0–12.4), wound (6.2%, 95% CI: 5.3–7.1), osteoarthritis (4.6%, 95% CI: 3.8–5.4) and claw injury (4.2%, 95% CI: 3.4–5.0). Conclusions These findings highlight the greyhound as a relatively common pet dog breed in the UK, accounting for 0.6% of dogs under primary veterinary care. Dental disease, trauma and osteoarthritis were identified as common health issues within the breed. Knowledge of common disorders can help greyhound breeders and regulators to prioritise breeding, rearing and racing management to mitigate some of the most prevalent issues. Greyhound rehoming organizations can also better inform adopters about prophylactic care.